Voluntary salt intake by feedlot steers - Harbers, L.H.; Warren, L.C. (Kansas State University. Agricultural Experiment Station, 2011)
Because it is a standard practice, adding salt to livestock rations has not received much attention in the past several years. Salt is universally added at 0.5% of the diet, but studies here in the early 50’s showed salt needs of cattle are related to dietary roughage levels.
Keywords: Beef; Salt intake; Feedlot steers